Trends in primary apartments market during COVID-19 pandemic - Jach, Wioletta; Hubar, Yurii; Trojański, Piotr; Maciuk, Kamil (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
The work includes an analysis of the primary real estate market in Cracow in 2017‑2020. The above analysis was carried out on the basis of transactions obtained from the official register at the city hall. The results of the research made it possible to observe the changes taking place in the market: the prices grew moderately, and the number of transactions was between 8,000 and 11,000 each year. In 2020, due to the COVID-19 pandemic, the number of transactions conducted dropped sharply. Despite the reduced interest of potential buyers, prices per square meter of residential space increased significantly during the period under review. Thus, the pandemic only affected the number of transactions and not the average price per unit of space.